MURAL BUDAYA DI KAWASAN DESA WISATA AIR TERJUN GREMBENGAN, DESA BONGAN, KABUPATEN TABANAN - Ni Nyoman Sri Rahayu; Kadek Risna Puspita Giri; Ni Luh Gde Niti Swari (Jurnal Lentera Widya, 2021)
Mural is well known as a wall design. The community service was carried out by the IDB Bali Lecturer Team in Bongan village, Tabanan. The community service program in the form of community service activities that will be carried out is in the form of mural activities located in the area of the road to Grembengan Waterfall Tourism, Bongan Tabanan Village. The walls to be mural have a length of 40 meters with a height of 2.8 meters and 140.8 meters for the total area. There were moral and social messages in people's lives with a visual approach in the form of displaying local Balinese culture, and containing messages or social criticism, one of which is related to the pandemic. The mural image shows a boy wearing a mask sweeping the yard and the others washing their hands. It is hoped that this image can be informative enough for visitors so that visitors can get used to living clean and healthy. The mural is done using the conventional method, by painting it, so as to bring out the aesthetic side of the mural that is more expressive. This is inseparable from the ability and the results of the paint scratches that are displayed.